Impacts of Real-Time Passenger Information Signs in Rail Stations at the Massachusetts Bay Transportation Authority. Issue 1 (January 2014) - Chow, William; Block-Schachter, David; Hickey, Samuel
Real-time information systems have been used in transit agencies around the world to inform passengers better of their estimated wait. In 2012, the Massachusetts Bay Transportation Authority (MBTA) activated new real-time information signage across its heavy rail system. These signs displayed the estimated arrival of the next two trains in each direction. The study reported in this paper examined whether the introduction of realtime arrival signage led to reduced expectations of wait time, improved satisfaction with MBTA, and increased ridership. In-station surveys were conducted before and after real-time information was introduced to gauge changes in passenger satisfaction and wait-time expectations. These expectations were compared against headways collected from automated train tracking data. Ridership changes were measured with automated fare collection data provided by MBTA. Survey results revealed that, after the introduction of the countdown signs, people reduced their overestimation of wait time by 50%. Satisfaction with MBTA did not change significantly as a result of the real-time signage. People reported that they felt more relaxed with real-time signage if the next train arrival occurred within a scheduled headway but less relaxed in cases in which the headways were much greater than scheduled. Minor improvements in ridership were detected in stations with the real-time information after other factors were controlled for, but these results were preliminary. This study suggests that real-time arrival signage would be a positive addition to heavy rail systems to increase passenger comfort and improve perceptions of system performance in a relatively cost-effective manner with the use of existing technologies.